Answers

2014-06-15T20:42:49+05:30
Tan50-tan40=2tan10
tan50=2tan+tan90
tan50=tan[40+10]
we have tan[a+b]=[tan a+tan b]
                           [1-tan a tan b]
=tan[40+10]=[tan40+tan10]
                    [1-tan40 tan10]
=tan50=[tan40+tan10]
             [1-tan40tan10]
=tan50[1-tan40tan10]=tan40+tan10
=tan50-tan50tan40tan10=tan40+tan10....and
tan50=tan[90-40]=cot40
=tan50-cot90tan40tan10=tan40+tan10
=tan50-tan10=tan40+tan10
because cot90=1
                     tan40
=tan50=tan40+2tan10
 .
· · tan50-tan40=2tan10

i hope u have understood.....if u like mark as the best......


9 4 9